Suicidal Behaviour among School-Going Adolescents in Saint Lucia: Analysis of Prevalence and Associated Factors - Jacob Owusu Sarfo; Mustapha Amoadu; Paul Obeng; Newton Isaac Gbordzoe; Timothy Pritchard Debrah; Crescens Osei Bonsu Ofori; John Elvis Hagan (Behavioral Sciences, 2023)
Suicide poses a debilitating threat to adolescents’ lives worldwide. Although suicide prevention efforts are evident globally, there is limited evidence on the prevalence and correlations of suicidal behaviour among school-going adolescents in Saint Lucia. We used a dataset from the 2018 Global School-based Student Health Survey to examine the prevalence and associated factors of suicidal behaviour among 1864 students from schools in Saint Lucia. Prevalence rates of 25.5%, 22.1%, and 17.5% were found for suicidal ideation, suicide plan, and suicide attempt, respectively. After adjusting for other factors, being male and having understanding parents were protective against suicidal behaviour. However, suicidal ideation was predicted by being physically attacked and bullied, parental guidance, tobacco use, loneliness, and worry. Moreover, being a victim of physical attacks and bullying, having close friends, being lonely, and worrying were predictive of making suicidal plans among adolescents. Attempting suicide was predicted by cigarette smoking, current use of tobacco and related products, bullying, having close friends, being lonely, and worrying. School-based preventive interventions are required to help address triggers of suicidal behaviour among adolescents in Saint Lucia and to help attain the targets for suicide prevention in the global Sustainable Development Goals.